Inventories in National Economies A Cross-Country Analysis of Macroeconomic Data - Chikán, Attila (Springer London, 2018)
This book introduces a new approach in the field of macroeconomic inventory studies: the use of multivariate statistics to evaluate long-term characteristics of inventory investments in developed countries. By analyzing a 44-year period series of annual inventory change in percentage of GDP in a set of OECD countries, disclosing their relationship to growth, industry structure and alternative uses of GDP (fixed capital investments, foreign trade and consumption), it fills a gap in the economic literature. It is generally accepted that inventories play an important role in all levels of the economy. However, while there is extensive literature on micro- (and even item-) level inventory problems, macroeconomic inventory studies are scarce. Both the long-term processes of inventory formation and their correlation with other macroeconomic factors provide interesting conclusions about economic changes and policies in our immediate past, and present important insights for the future.